Caspase-8 as a Therapeutic Target in Cancer - Stupack, Dwayne G. (2010)
Caspase-8 is an apical caspase which initiates programmed cell death following death receptor ligation. This central role in apoptosis has prompted significant clinical interest in regulating caspase-8 expression and proteolytic activity. However, caspase-8 has also been found to play a number of non-apoptotic roles in cells, such as promoting activation NFκB signaling, regulating autophagy and altering endosomal trafficking, and enhancing cellular adhesion and migration. Therefore, depending upon the specific cellular context, caspase-8 may either potentiate or suppress tumor malignancy. Accordingly, a marked heterogeneity exists in the expression patterns of caspase-8 among different tumor types. Therapeutics have been developed which can increase caspase-8 expression, yet it remains unclear whether this approach will be beneficial in all cases. Care is warranted, and the role of caspase-8 should be addressed on a case by case basis.